Parental Attachment and Peer Support as Predictors of Adolescents’ Psychological Well-Being at X Junior High School, Yogyakarta - Alfarina, Ria; Jannah, Raudhatul (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study predicts the role of parental attachment and peer support in adolescent psychological well-being among students at SMP